Efficient hydrogen production by microwave-assisted catalysis for glycerol-water solutions via NiO/zeolite-CaO catalyst - Husni, Husin; Erdiwansyah, Erdiwansyah; Ahmadi, Ahmadi; Fahrizal, Nasution; Rinaldi, Wahyu; Abnisa, Faisal; Rizalman, Mamat (Elsevier B.V., 2022)
Hydrogen from glycerol is one of the most potent green energy sources to replace fossil fuels. Thus, converting a glycerol solution to hydrogen through microwave-assisted catalysis is continuously gaining interest from researchers worldwide. The research aim was to combine NiO/zeolite and CaO for efficient hydrogen production from glycerol-water solution via microwave-assisted. The BET, XRD, and TEM were applied to characterize the properties of the NiO/zeolite-CaO catalyst. The influence of CaO content on NiO/zeolite (NiO/zeolite-CaO) catalyst, and microwave power on glycerol-water decomposition into hydrogen were investigated systematically. The catalytic performance for hydrogen production from glycerol-water solution was conducted in a fixed bed quartz-tube flow reactor via microwave irradiation a fed flow-rate (FFR) of 0.5 ml/min. Several characteristics, such as heating rate of 300–600 W, have been studied, CaO content of 10 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%, and 100 wt.%, respectively. The combined utilization of NiO/zeolite and CaO was efficient in obtaining more hydrogen production. Furthermore, the maximum conversion was found to be around 98.8%, while the highest hydrogen purity was found to be up to 96.6% when 20 wt.% NiO was used as an active site on natural zeolite and 50 wt.% CaO was used.